The effect of the course review horay learning model on students' mathematical reasoning abilities - Dalimunthe, Anggi Syah Putri; Siregar, Tanti Jumaisyaroh (Desimal: Jurnal Matematika, 2022)
Mathematics is a science that is acquired through reason because one of the goals of mathematics education is for students to develop the ability to reason. The purpose of this research is to determine the effect of the Course Review Horay learning model on students' mathematical reasoning abilities. This research is a type of quantitative research. The sampling strategy of cluster random sampling was used to select the sample in this research. The instrument used to collect data is a test of mathematical reasoning abilities in the form of description questions. Normality test, homogeneity, and hypothesis testing with t-test are part of the data analysis approach of this research. Based on the results of the t-test analysis, the results obtained sig. (2-tailed), where the result is 0.000 which is smaller than 0.05. So, it can be concluded that there is an effect of the Course Review Horay learning model on students' mathematical reasoning abilities.